Influence of Fertilizer Source and Rate on Buffalograss Divot Recovery - E. Alderman; J. Hoyle; J. Fry; S. Keeley (Kansas Agricultural Experiment Station Research Reports, 2015)
Application of quick-release nitrogen fertilizer increased buffalograss divot recovery. A quick-release fertilizer at 1 lb N/1,000 ft2resulted in 50% divot recovery 6.3 days quicker compared to the untreated control.
Keywords: turfgrass; fertilizer source; fertilizer rate; buffalograss; divot recovery; quick-release fertilizer